Management of an intranet for the Inspectorate of Education - Brufau Galitó, Jaume (Avances en Supervisión Educativa, 2008)
It is more and more necessary for an inspector of education to have full access to information about the schools under his supervision duties in order to report and counsel properly and efficiently.The Internet offers these professional, as well as others, an opportunity of access to the suitable information for everyday tasks, including matters' dealing and management.At the Inspectorate of Education in Lleida, we are carrying out a professional experiment of on-line management with base on an internal net It is PHP-programed  and has a  MSQL data base included in a XTEC server of the Education Department in Catalonia's autonomous government.